Leviviricetes: expanding and restructuring the taxonomy of bacteria-infecting single-stranded RNA viruses - Callanan, Julie; Stockdale, Stephen R.; Adriaenssens, Evelien M.; Kuhn, Jens H.; Rumnieks, Janis; Pallen, Mark J.; Shkoporov, Andrey N.; Draper, Lorraine A.; Ross, R. Paul; Hill, Colin (Microbial genomics, 2021)
The vast majority of described prokaryotic viruses have double-stranded or single-stranded DNA or double-stranded RNA genomes. Until 2020, a mere four prokaryotic single-stranded, positive-sense RNA viruses have been classified in two genera ( Riboviria; Lenarviricota; Allassoviricetes; Leviviridae ). Several recent metagenomic and metatranscriptomic studies revealed a vastly greater diversity of these viruses in prokaryotic soil communities than ever anticipated. Phylogenetic analysis of these newly discovered viruses prompted the reorganization of class Allassoviricetes , now renamed Leviviricetes , to include two orders, Norzivirales and Timlovirales , and a total of six families, 428 genera and 882 species. Here we outline the new taxonomy of Leviviricetes , approved and ratified in 2021 by the International Committee on Taxonomy of Viruses, and describe open-access hidden Markov models to accommodate the anticipated identification and future classification of hundreds, if not thousands, of additional class members into this new taxonomic framework.